Höflichkeitsstrategien der Imagepflege von Ärztinnen und Ärzten – eine Analyse von ärztlichen Antworten auf negative Bewertungen auf Arztbewertungsportalen - Kałasznik, Marcelina; Waliszewska, Karolina (Moderna Språk, 2023)
In the digital age, people are confronted with new emerging communicative practices. Doctors as a professional group are not spared from this. For some time now, doctor rating portals have been developing, which present doctors with a new situation of being rated by patients on the Internet. In addition, the doctor rating portals encourage doctors to contact their patients online. With this in mind, our article focuses on negative reviews of gynaecologists that were published by patients on the jameda.de portal. The main goal is to answer the question of how doctors react to negative comments from patients that may threaten their image. The corpus of the study includes over 70 negative reviews and over 70 responses from physicians. That being said, the article characterizes medical reactions to negative evaluations and examines them from the perspective of speech act theory. We pay particular attention to the expressive speech acts REGRET, EXCUSE (ONESELF), THANK and WISH, which are remarkably frequent in the corpus. They serve to defuse the conflicting situation that has arisen as a result of negative evaluation and to save the doctor’s image despite negative evaluation.